Alexander Blok, the German “Conservative Revolution” and the Russian Avant-Garde - Rykov, Anatolii V. (Actual Problems of Theory and History of Art, 2017)
The paper examines the political aspects of Alexander Blok’s poetry and critical works. The main focus is on the heritage of the German “Conservative Revolution” and its influence on Blok’s oeuvre. The authordraws a comparison between one of the most radical Blok’s papers — “The Decline of Humanism” (1919) and Nikolay Punin’s and Evgeny Poletayev’s protofascist tract “Against Civilization” (1918). Special attention is paid to the discourses of war and struggle in Blok’s poetry and criticism. The article considers the special ways of convergence of Symbolist and Futurist aesthetics in the Russian avant-garde in the contexts of racism andnationalism. It explores Blok’s views on art and politics as the Russian equivalent of the protofascist theories of regeneration (for instance, Richard Wagner’s and Houston Stewart Chamberlain’s conceptions). The papertraces the biological metaphors in Blok’s poetry and publications, their role in the development of his populist, anti-intellectualistic aesthetics. It concerns the racist, sexist, and classist connotations of Blok’s works in relation to the general issues of avant-garde art interpretation. The author draws the conclusion that “The Decline of Humanism”, as one of the theories of romantic anti-capitalism, combines the elements of Social Darwinism and eugenics, close to the rhetoric of the German “Conservative Revolution” and proto-fascist discourses in European culture of that period.
Keywords: Alexander Blok; Nikolay Punin; Evgeny Poletayev; conservative revolution; politics; racism; proto-fascism; Modernism; avant-garde